Antidepressant and Anxiolytic-Like Effects of the Stem Bark Extract of Fraxinus rhynchophylla Hance and Its Components in a Mouse Model of Depressive-Like Disorder Induced by Reserpine Administration - Kim, Yu Ri; Park, Bo-Kyung; Seo, Chang-Seob; Kim, No Soo; Lee, Mi Young (Frontiers in Behavioral Neuroscience, 2021)
There is an urgent need to find antidepressants that can be administered for long periods without inducing severe side effects to replace conventional antidepressants that control monoamine levels, such as tricyclic antidepressants (TCAs), monoamine oxidase inhibitors (MAOIs), and selective serotonin reuptake inhibitors (SSRI). We sought to determine the antidepressant effects of Fraxinus rhynchophylla Hance (F. rhynchophylla Hance, FX) and its components on a reserpine-induced mouse model. One hour after oral administration of FX (30, 50, and 100 mg/kg), esculin (50 mg/kg), esculetin (50 mg/kg), fraxin (50 mg/kg), and fluoxetine (20 mg/kg), reserpine was delivered intraperitoneally to mice. Behavioral experiments were conducted to measure anxiety and depressive-like behaviors after 10 days of administration. FX and its components increased the number of entries into the center of an open field as well as distance traveled within it and decreased immobility duration in the forced swim and tail suspension tests. Reserpine-induced increases in plasma corticosterone concentrations were attenuated by the administration of FX and its components, which were also found to decrease the reserpine-induced enhancement of mRNA levels of interleukin (IL)-12 p40, IL-6, and tumor necrosis factor (TNF)-α, pro-inflammatory cytokines. Finally, the diminished expressions of hippocampal phosphorylated cAMP response element-binding protein and brain-derived neurotrophic factor by reserpine were increased by FX and its components. Our results suggest that FX and its components regulate anxiety and depressive-like behaviors through stress hormones, immune regulation, and the activation of neuroprotective mechanisms, further supporting the potential of FX and its components as antidepressants.